ECONOMETRIC EXAMINATION OF THE IMPACT OF INCOME ON HOUSEHOLD EXPENDITURES FOR PACKAGE HOLIDAYS IN SERBIA - Hanić, Hasan; Bugarčić, Milica; Lukić, Radojko (The European Journal of Applied Economics, 2021)
The subject of this paper is the econometric examination of the impact of income on expenditures, i.e. on the demand for package holidays of households in Serbia. The aim of this paper is to quantify the impact of income on household expenditures for package holidays in the country and abroad on the basis of alternative functional forms of Engel curves and elasticities derived from them. The starting research hypothesis is that with the increase in household income, the share of expenditures for tourist arrangements in total household expenditures in Serbia remains approximately unchanged. As sources of data, Household Budget Surveys in Serbia were used, which were conducted every year, starting from 2006 (until 2019). Based on the different functional forms of Engel curves, the parameters of the impact of income on expenditures for package arrangements were estimated, and then income elasticities were estimated. In addition to the impact of income, the impact of qualitative characteristics of households and especially household heads on expenditures for tourist arrangements was examined. With the help of appropriate statistical tests, the basic research hypothesis was proven and the influence of socio-economic and demographic characteristics of households on the demand for package holidays was quantified.